Burnett County comprehensive planning public opinion survey report - Hadley, Shelly; Trechter, David (My University, 2009)
The motivation for this study was to gather opinions of residents and property owners about the future direction of development in Burnett County. Foth Infrastructure and Environment, LLC and Burnett County chose to work with the SRC to process, compile, and analyze the results of this survey.
28 p.
Keywords: Public opinion survey; Community planning; Comprehensive plan report; Comprehensive plan; Burnett County comprehensive plan; Burnett County, Wisconsin; Burnett County (Wis.); Burnett County (Wis.)--Surveys; Public opinion--Wisconsin--Burnett County; Land use--Wisconsin--Burnett County; Regional planning--Wisconsin--Burnett County